Menguak Kekuatan Tindak Tutur Quote Inspiratif KHR. Ahmad Azaim Ibrahimy - Yulia Tutik Nurfia (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to uncover the power of speech acts in inspirational quotes by KHR. Ahmad Azaim Ibrahim. Using a qualitative approach, this study analyzes various quotes produced by this figure and explores their meaning and impact on society. Text analysis methods are used to understand the social, cultural, and psychological contexts behind each quote. The results show that the speech acts in these quotes function not only as motivation but also as tools for shaping positive thought patterns and behaviors. The implications of these findings demonstrate the important role of language in building public awareness and enthusiasm. This research is expected to contribute to the development of linguistics and social psychology studies, as well as encourage the use of inspirational language in everyday life.